Is CO2 injection at Aquistore aseismic? A combined seismological and geomechanical study of early injection operations. (August 2018) - Stork, A.L.; Nixon, C.G.; Hawkes, C.D.; Birnie, C.; White, D.J.; Schmitt, D.R.; Roberts, B.
Highlights: Seismic monitoring has not revealed any injection induced seismicity at the Aquistore CO2 storage project. An extensive seismic network of surface broadband stations, and near-surface and downhole geophones has been in place to monitor injection. Geomechanical modelling suggests effective stress changes at an identified fault near the injection well are too small to induce seismicity. Abstract: Fluid injection is known to induce seismic events if the injection causes fracturing of the surrounding rock or if resulting pressure changes reactivate pre-existing faults and fractures. Carbon dioxide (CO2 ) storage projects where CO2 is injected into deep geological formations for permanent containment are one sector where induced seismicity has been observed. The Aquistore storage project in Saskatchewan, Canada began CO2 injection into the basal Cambrian sandstone at ∼3.2 km deep in April 2015 and the site has been extensively monitored for seismicity. Passive seismic monitoring instrumentation includes a small network of broadband seismometers, a continuously recording array of near-surface geophones and temporary deployments of downhole geophones at depths from 2950 m to 3010 m in an observation well. To date no injection-related induced seismicity has been observed. The seismic arrays are functioning as expected and local mine blasts, orientation shots and perforation shots have been detected using standard detection algorithms. Data stacking algorithms have also been tested on short-periods of data. Using synthetic data added to noise models, the estimated minimum detectable event local magnitude is −0.8 for the broadband stations and between −1.6 and −0.6 for the near-surface geophones. Thus far, small volumes of CO2 have been injected at Aquistore (∼140 kt) and injection has generally occurred below the fracture pressure. As a result, predicted pore pressure changes are small and periods without injection have allowed relaxation of the pressure plume. Geomechanical modelling suggests insignificant effective stress changes at an identified fault near the Aquistore injection well. It is therefore not surprising that no induced seismicity has been detected. With further injection, continued seismic monitoring is essential to provide warning of any fault reactivation and thus any potential increase in seismic risk or CO2 leakage risk.